Surgical management of large acoustic neuromas: a review - Philip, Rajan; Prepageran, Narayanan; Raman, R.; Jennifer, L.P.H.; Waran, V. (Malaysian Medical Association, 2009)
Acoutic neuromas operated at UMMC from 2001 to 2006 were retrospectively reviewed. There were a total of 27 cases. All tumors were large, measuring more than 2 cm. Hearing loss was the most common presenting symptom (63%), followed by headache (52%), dysequilibrium (30%), facial numbness (30%), tinnitus (26%) and gait disturbances (15%). Eleven (41%) of patients had hydrocephalus at the time of presentation, for which a shunt procedure was required. The translabrynthine (TL) approach was used for 12 patients and the retrosigmoid (RS) with or without presigmoid clearance for the remaining 15. Major complications included one mortality and three cerebrovascular accidents (CVA's). The one-year facial nerve outcome was good to acceptable in 62% (House-Brackmann Grade I - IV) of patients. A literature review of current management of acoustic neuromas is presented.